Identification “Merdeka Curriculum” of Elementary School Levels in Tomohon City - Mamuaja, Marlin Penina; Katuuk, Deitje Adolfien; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
The "Merdeka Curriculum" Elementary School is a curriculum that allows elementary schools to create a curriculum that is adapted to the conditions and needs of each school. This study aims to identify the level of implementation of the Merdeka curriculum in Elementary Schools in Tomohon City. The method used in this study was a survey method using a questionnaire that was distributed to 21 elementary schools in Tomohon City. The results showed that the level of implementation of the Merdeka curriculum of the Elementary School in Tomohon City was relatively high, with an average implementation score of 78.5%. Factors that influence the performance of this curriculum include teacher competence in developing the curriculum, support from the school principal, and adequate facilities and infrastructure. This research is expected to provide helpful information for developing and implementing the Merdeka curriculum of Elementary Schools in Tomohon City and other areas.